Maintaining Social Harmony Through Leech’s Neg-Politeness: An Analysis of the Persuasion Movie Adaptation - Indrawati, A.A. Made; Maharani, Putu Devi (Journal of Language and Literature Studies, 2025)
Language is used to convey message in digital platform such as movie. Persuasion movie is based on Jane Austen’s novel which is rich of polite language considering this movie take Regency-era as the background. In this era, social status, age, gender are become aspects the language use. This study aims to find the utterance which consist of maxim in Neg-Politeness by Leech (2014) that delivered by the characters in Persuasion movie 2022 version. This research uses qualitative research method with descriptive approach through an observation since analyzing the data of Neg-Politeness requires context of situation. Other than that, this approach can lead into a deeper analysis and explanation of the language use and chosen word by the speaker, then linking it to the background context through paragraph structure. The data collection arranged with library method and followed by observation while note-taking. The result shows that there are 18 utterances that consist of Neg-Politeness, they are 5 utterances of Tact Maxim, 3 utterances of Modesty Maxim, 7 utterances of Obligation Maxim, 2 utterances of Opinion Reticence Maxim, and 1 utterance of Feeling Reticence Maxim. In order to maintain the social harmony and maintain relationship among the society, Obligation maxim is the most used maxim which applied in the dialogue of Persuasion movie since the background setting of this movie is in Regency Era where the social class impacting the language use. Most of the characters applied this maxim because they can less burden of feeling uneasy while maintaining the social harmony.